Combating powdery mildew: Advances in molecular interactions between Blumeria graminis f. sp. tritici and wheat - Mapuranga, Johannes; Chang, Jiaying; Yang, Wenxiang (Frontiers in Plant Science, 2022)
Wheat powdery mildew caused by a biotrophic fungus Blumeria graminis f. sp. tritici (Bgt), is a widespread airborne disease which continues to threaten global wheat production. One of the most chemical-free and cost-effective approaches for the management of wheat powdery mildew is the exploitation of resistant cultivars. Accumulating evidence has reported that more than 100 genes/alleles in 63 loci (Pm1-Pm68) wheat powdery mildew resistance genes have been identified from common wheat and its wild relatives, and only a few of them have been cloned so far. However, continuous emergence of new pathogen races with novel degrees of virulence renders wheat resistance genes ineffective. An essential breeding strategy for achieving more durable resistance is the pyramiding of resistance genes into a single genotype. The genetics of host-pathogen interactions integrated with temperature conditions and the interaction between resistance genes and their corresponding pathogen avirulence genes or other resistance genes within the wheat genome determine the expression of resistance genes. Considerable progress has been made in revealing Bgt pathogenesis mechanisms, identification of resistance genes and breeding of wheat powdery mildew resistant cultivars. A detailed understanding of the molecular interactions between wheat and Bgt will facilitate the development of novel and effective approaches for controlling powdery mildew. This review gives a succinct overview of the molecular basis of interactions between wheat and Bgt, and wheat defense mechanisms against Bgt infection. It will also unleash the unsung roles of epigenetic processes, autophagy and silicon in wheat resistance to Bgt.